Transient Estrogen Receptor Binding and p300 Redistribution Support a Squelching Mechanism for Estradiol-Repressed Genes - Guertin, Michael J. (Endocrine Society, 2014)
Proper gene regulation is essential for proper organismal development and appropriate responses to external stimuli. Specialized factors, termed master regulators, are often responsible for orchestrating the molecular events that result from signaling cascades. Master regulators coordinate the activation and repression of specific gene classes. Estrogen receptor α (ER) precipitates the signaling cascade that results from endogenous or exogenous estrogen hormones. ER is a classic transcriptional activator and the mechanisms by which ER coordinates gene activation are well characterized. However, it remains unclear how ER coordinates the immediate repression of genes. We integrated genomic transcription, chromosome looping, transcription factor binding, and chromatin structure data to analyze the molecular cascade that results from estradiol (E2)-induced signaling in human MCF-7 breast cancer cells and addressed the context-specific nature of gene regulation. We defined a class of genes that are immediately repressed upon estrogen stimulation, and we compared and contrasted the molecular characteristics of these repressed genes vs activated and unregulated genes. The most striking and unique feature of the repressed gene class is transient binding of ER at early time points after estrogen stimulation. We also found that p300, a coactivator and acetyltransferase, quantitatively redistributes from non-ER enhancers to ER enhancers after E2 treatment. These data support an extension of the classic physiological squelching model, whereby ER hijacks coactivators from repressed genes and redistributes the coactivators to ER enhancers that activate transcription.